2019
DOI: 10.1016/j.ijid.2019.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Zika Syndrome: Prevalence of low birth weight and associated factors. Bahia, 2015–2017

Abstract: Objective: The clinical manifestations of Congenital Zika Syndrome (CZS) are not fully known, for example its effect on birth weight. This study estimated the prevalence of low birth weight (LBW) among children with CZS, and identified associated factors. Methods: Cross-sectional study involving 393 children with CZS living in Bahia, Brazil, in 2015-2017. Official Information Systems were the data sources. We calculated LBW prevalence and applied Logistic Regression to assess associated factors. Results: Preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
3
18
0
2
Order By: Relevance
“…Body weight reduction is a clear sign of intrauterine growth restriction, a condition that was described as part of CZS in humans (7,34,35) and mouse models (5,6). Recently, a survey showed that the prevalence of low birth weight is four times higher in CZS children compared to other newborns from the same region (36). In our assays, we found body weight reduction in infected malnourished litters, consistent with the findings in human CZS cases.…”
Section: Discussionsupporting
confidence: 91%
“…Body weight reduction is a clear sign of intrauterine growth restriction, a condition that was described as part of CZS in humans (7,34,35) and mouse models (5,6). Recently, a survey showed that the prevalence of low birth weight is four times higher in CZS children compared to other newborns from the same region (36). In our assays, we found body weight reduction in infected malnourished litters, consistent with the findings in human CZS cases.…”
Section: Discussionsupporting
confidence: 91%
“…Low birthweight and intrauterine growth restriction were common findings in the studies in the current review [19,63,64,69,82,85,[89][90][91], representing a risk for children exposed to ZIKV during pregnancy. A recent study found that prevalence of Low birthweight in infants with CZS was more than four times that of the overall sample of live births [144].…”
Section: Plos Onementioning
confidence: 96%
“…The percentage of infants with a birth weight of < 2500 g in the group without microcephaly was 7 %, but the percentage increased to 48 % in the group with microcephaly, evidencing a strong association between low birth weight and microcephaly. A previous study conducted in the state of Bahia showed a 37.2 % prevalence of low birth weight in newborns with congenital ZIKV syndrome, including microcephaly [23]. In a study carried out in Guatemala, a birth weight of < −1 standard deviation and small for gestational age were associated with microcephaly [24].…”
Section: Variable Adjusted Odds Ratiomentioning
confidence: 83%